DESIGN OF GRAVITY BASED MATERIAL CONVEYOR EQUIPMENT - Mr. SANTOSH NARAYAN LOKHANDE; Mr. SUNIL PAGARE; DR. S. RAM REDDY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Industrial automation in recent decade has demonstrated to be the effective way of development of performance in industrial system. The results of the research carried out for optimization of the industrial processes in last decade leads to the implementation of automation in large industries. The small industries are still waiting for the low price systems for process enhancement. The small industries have the opportunities to partially replace the present system with automated system, by considering the cost limitations. Handling the material is one of the main features of the production industries and it holds 25% shares of the production cost of any product. The conveyor with the adjustable length feature and high mass handling capacity becomes the basic need for development of the automation system during the production for managing the material. Authors have developed and presented the conveyor for material flow on the basis of gravity.